New-onset atrial fibrillation and warfarin initiation: High risk periods and implications for new antithrombotic drugs - Garcia, David A.; Lopes, Renato D.; Hylek, Elaine M. (Thrombosis and Haemostasis, 2010)
Atrial fibrillation is a common condition that increases the risk of stroke in many patients. Although warfarin has been shown to reduce the risk of stroke, many patients who might benefit from anticoagulation do not receive this therapy. Fear of bleeding is the most often cited reason. Several new anticoagulant medications are being studied to determine their efficacy and safety relative to warfarin. Unlike earlier trials that established the superiority of warfarin over placebo, recent trials in atrial fibrillation have enrolled a disproportionate number of patients already taking warfarin. This review suggests that the risk of both haemorrhage and stroke are highest when atrial fibrillation is newly diagnosed and during the initiation of anticoagulant medication. Randomised controlled trials designed to evaluate the safety and efficacy of new anti-thrombotic agents should include substantial numbers of patients without prior exposure to anticoagulation since these individuals are at the highest risk for bleeding and thromboembolism.
Keywords: Clinical trials; oral anticoagulants; thrombosis; stroke prevention; heart